New Route for the Synthesis of Pyrimido[4’,5’:4,5]thiazolo[3,2-a]benzimidazol-4(3H)-ones - DAVOODNIA, A.; ESHGHI, H.; EZZATAHMADI, S.; TAVAKOLI-HOSEINI, N. (Asian Journal of Chemistry, 2010)
A new route for the synthesis of 2-arylpyrimido[4',5':4,5]thiazolo[3,2- a]benzimidazol-4(3H)ones has been developed through heterocyclization of 3-aminothiazolo[3,2-a]benzimidazol-2-carboxamide with aromatic aldehydes in boiling glacial acetic acid followed by air oxidation.